PENGARUH TERAPI PIJAT REFLEKSI KAKI TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI PRIMER - Rezky, Rindang Azhari; Hasneli, Yesi '; Hasanah, Oswati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The objective of this study was to identify the effect of foot reflexology theraphy on the blood pressure in patients with primary hypertension. This study used quasy experiment design with non-equivalent control group approach. This study was conducted at Puskesmas Lima Puluh with 30 people as the sample which was divided into 15 people experiment group and 15 people control group. The experiment group was given foot reflexology massage theraphy of 15 minutes a day for three days consecutively. A digital sphygmomanometer and observation sheet were used as the measurement instruments. The analyses used were univariate analysis to observe the frequency and bivariate analysis with Dependent T-test and Independent T-test. The result of the study showed a decrease of 6,29 mmHg on the experiment group patients systolic blood pressure and a decrease of 3,44 mmHg on the diastolic blood pressure. The result of statistical test indicated a significant decrease on the experiment group with p value 0,000 (p<0,05). The result of this study indicates that foot reflexology massage theraphy can lower patients blood pressure even though the patients are still under hypertension category.